Development of financial support for Ukraine’s green transition based on Poland’s experience with green bonds - Ryszawska, Bozena; Kuznetsova, Svitlana; Manoylenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process of designing of financial instruments the green energy transition of the national economy in Ukraine based on the replication of the Polish experience of issuing green bonds. At present, there are significant gaps in building a financial instruments Ukraine’s green energy transition. Replication of the Polish experience of using green bonds, as well as their issuance and circulation, becomes the basis for expanding the financial framework for the energy transition of the national economy. An analysis of the dynamics in the issuance of green bonds in the global and local Polish financial markets has been conducted; factors that determine their cost at issue were identified based on the application of a regression model. It was established that the key factor affecting the cost of green financing is the scale of the issue, which increases its liquidity and allows them to be included in the portfolios of international institutional investors. Based on a comparison of the institutional environment of the issuance of green bonds in Poland and Ukraine, directions for its improvement for the Ukrainian national economy have been identified. Special feature of the results is the combination of quantitative analysis of issuance parameters with institutional support for the development of green financing markets in Poland and Ukraine. That made it possible not only to identify key factors affecting the assessment of the value of green capital but also to substantiate the directions for improving the institutional support for financing the green transition for the Ukrainian economy. The results could be implemented provided that the current legislation is improved to ensure external verification, the development of mechanisms for guaranteeing and insuring risks, as well as the orientation of issuances to large reconstruction and energy transition projects